Barriers to Stereoinversion of N-Aryl-1,3,2-benzodithiazole 1-Oxides Studied by Dynamic Enantioselective Liquid Chromatography - Oxelbark, Joakim; Allenmark, Stig (Journal of organic chemistry, 1999)
Free energies of activation for the enantiomerization of a series of racemic N-aryl-1,3,2-benzodithiazole 1-oxides have been determined by dynamic high-performance liquid chromatography (DHPLC) on a chiral stationary phase. From a comparison of experimental and computer-simulated chromatograms, the barriers to stereoinversion at sulfur were found to be around 80 kJ/mol and relatively insensitive to effects from substituents in the N-aryl group. Throughout the series the (+)-forms (436 nm) were found to be of (S)-configuration.